"Centrum przeciwko Wypędzeniom" w świetle głównych filarów polityki powojennych Niemiec. Polsko-niemieckie aspekty skomplikowanego dialogu = "Centre against expulsions" in light of chief fundamentals of post-war german politics: Polish-German aspects of a complicated dialogue - Müller, Hans-Peter (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author attempts at proving that the recent discussion on Berlin`s "Centre against Expulsions" should not be considered without taking into account debates dealing with the Nazi regime as well as standpoints resulting from "raison d`etat" in Eastern and Western Germany. In the case of Poland, the issue of resettlement constitutes a special test for Germany as far as dealing with the past is concerned.
Keywords: Centrum przeciwko Wypędzeniom; przesiedlenia ludności; stosunki polsko-niemieckie; historia; od 1945 r.